Circuit models of lossy coaxial shielded cables connected to non-linear loads to analyze radiated and conducted susceptibilities. Issue 7 (31st January 2017) - Saih, Mohamed; Rouijaa, Hicham; Ghammaz, Abdelilah
Abstract : This paper studies the variation effects of incident plane wave on shielded coaxial cables, using Branin's method, which is called the method of characteristics. That model can be directly used for the time- and frequency-domain analyses. Moreover, it had the advantage of being used without the need of setting the preconditions of the charges applied to its ends. This makes it easy to insert in circuit simulators, such as SPICE, SABER, and ESACAP. The results obtained under ESACAP were remarkably similar to other results, which reinforce the validity of the model. Finally, we will discuss the effects of the variation of the incident plane wave.